Upaya Pencegahan Smartphone Addicted Berbasis Vocabulary Word Match Game Pada Anak Usia Sekolah Dasar Desa Tumi Jaya Oku Timur - Zulaikah Zulaikah; Hastuti Retno Kuspiyah; Khusnatul Amaliah; Eka Setya Ningsih; M. Ilham Abdillah; Sheila Oki Tarina (Jurnal Pengabdian Masyarakat (abdira), 2022)
The aim of this community service is to reduce addicted Smartphone by providing and introduction to mastery of English Vocabulary through the vocabulary word match game method for elementary school in Tumi Jaya Village, Jayapura OKU Timur. The method used is by using a word match game, this service program can be carried out well and run smoothly according to what has been planned from the beginning of the activity even though all service participants have not mastered the material well. This activity got a very good response with the evidence of the activeness of the service participants in participating in the learning process by not leaving the material before it was finished. The message conveyed by the leaders and parents of elementary school was that they must continued to hold follow-up activities in the form of similar training which are always held periodically so that they can improve their ability of elementary school in carrying out the learning process, especially in increasing vocabulary.